Breastfeeding and Growth of Children in the Peri/postnatal Epigenetic Twins Study (PETS): Theoretical Epigenetic Mechanisms. (August 2016) - Temples, Heide S.; Willoughby, Deborah; Holaday, Bonnie; Rogers, Curtis R.; Wueste, Daniel; Bridges, William; Saffery, Richard; Craig, Jeffrey M.
Background: The prevalence of overweight infants and toddlers has increased by 60% in the past 30 years and is a significant contributor to diabetes, cardiovascular disease, and early morbidity and mortality. The World Health Organization's updated meta-analysis in 2013 observed an association between breastfeeding and a lower prevalence of obesity later in life. The purpose of this study was to assess the growth of children in a cohort of Australian twins to examine associations between duration of breastfeeding and growth at 18 months of age. Our hypothesis is that the anthropometric measurements of the participants will be greater with shorter duration of breastfeeding. Methods: Methods include using cross-sectional data from a cohort at the 18-month visit (n = 179) in the Peri/postnatal Epigenetics Twins Study (PETS) to assess the relationship between duration of breastfeeding and infant size at 18 months of age. Inclusion criteria were birth weight of more than 2000 grams and breastfed for less than 1 month, 1 to 3 months, or 4 to 6 months. Results: The analysis suggested that infants breastfed for 1 to 3 months were significantly larger than infants breastfed for 4 to 6 months in terms of mean body mass index (BMI) (0.61 kg/m 2 ; P = .02; 95% confidence interval [CI], 0.17-1.05), arm circumference (0.66 cm; P = .006; 95% CI, 0.26-1.06), and abdominal circumference (1.16 cm; P = .03; 95% CI, 0.26-2.06). The analysis also suggested that infants breastfed for less than 1 month were significantly larger than infants breastfed for 4 to 6 months in terms of mean arm circumference (0.72 cm; P = .009; 95% CI, 0.26-1.17). Conclusion: Results suggest that supplementing with non–breast milk before 4 months of age was associated with an increased BMI, arm circumference, and abdominal circumference at 18 months of age. The mean BMI decreased from 85% to 65% when infants were breastfeeding for 4 to 6 months as compared to breastfeeding for 1 to 3 months. Breastfeeding for 4 to 6 months appeared to protect against the risk of obesity for the children in the PETS.